(untitled) (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
The aim of this research is to determine the role of the English Correspondence course in the Logistics Management Study Program at the Banyuwangi Maritime Academy. This research uses qualitative methods to explore the role of the English Correspondence course in the Logistics Management Study Program at the Banyuwangi Maritime Academy. Document analysis was used to review the curriculum, while interviews with lecturers provided teaching perspectives. Student surveys were used to evaluate course effectiveness. The results show that this course was successful in improving students’ English language skills, integrating logistics management, and developing soft skills and leadership skills. The results of this research state that the English Correspondence course in the Logistics Management Study Program at the Banyuwangi Maritime Academy has proven its success in forming competent students in the logistics industry. Increasing English language skills and integrating logistics management concepts creates an important balance, accompanied by the development of soft skills for future challenges.